Comparison of thromboelastographic profiles and clinical characteristics in children with severe Mycoplasma pneumoniae pneumonia - Li, Yong-tao; Ma, Yu-mei; Dai, Fu-li; Peng, Zhen; Dai, Ya-ping; Zhi, Ke; Feng, Hai-hong; Li, Shu-jun (Frontiers in Pediatrics, 2025)
BackgroundThis study aimed to compare Thromboelastographic (TEG) profiles and clinical characteristics between severe Mycoplasma pneumoniae (MP) pneumonia patients with normal and abnormal TEG parameters.MethodsThe clinical data of 133 children with severe MP pneumonia were retrospectively analyzed. Patients were divided into normal (n = 76) and abnormal (n = 57) TEG groups. Demographic characteristics, clinical manifestations, laboratory findings, imaging features, bronchoscopy results, treatment, complications, and outcomes were compared between groups.ResultsThe abnormal TEG group (42.9%) had longer fever duration (median: 8.5 vs. 7.0 days, P < 0.001) and hospital stay (median: 11.5 vs. 10.0 days, P = 0.003). They also showed higher levels of C-reactive protein (median: 30.2 vs. 20.1 mg/L, P < 0.001), lactate dehydrogenase (median: 334.5 vs. 276.0 U/L, P = 0.001), and D-dimer (median: 1.2 vs. 0.5 μg/ml, P < 0.001). HRCT revealed more lobar consolidation or multilobar involvement (36.8% vs. 18.4%, P = 0.016), and bronchoscopy showed more mucous plug obstruction (28.1% vs. 10.5%, P = 0.008) in the abnormal TEG group. TEG parameters indicated a hypercoagulable state with shorter R time (P < 0.001), shorter K time (P < 0.001), and higher MA (P = 0.003). The abnormal TEG group had higher incidences of coagulopathy (P < 0.001), cardiac involvement (elevated cardiac enzymes: 36.8% vs. 17.1%, P = 0.009; pericardial effusion: 10.5% vs. 1.3%, P = 0.017), and plastic bronchitis (P = 0.006). They also required longer azithromycin courses (median: 15 vs. 14 days, P = 0.026).ConclusionChildren with severe MP pneumonia and abnormal TEG profiles have more severe clinical manifestations, higher inflammatory markers, more extensive lung involvement, and a higher incidence of complications. TEG may help identify high-risk patients and guide management in severe MP pneumonia.